A critical analysis of A2 Fast Track Lowveld sugar cane farms in Zimbabwe in global value chains: interrogating the lives of farmers and farm labourers - Chingono, Kudakwashe Rejoice (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
The sugar cane industry has for many years been a lucrative business with a booming global market. In Zimbabwe, the sugar cane industry is no exception, as it has been regarded as one of the most efficient in the region and even in the world. The sugar cane farms and mills in Zimbabwe are located in Triangle and Chiredzi, in the south-eastern part of the country and they are under the ownership of Tongaat Hullet and the Zimbabwean A2 farmers. The focus of this is on the A2 fast track farms in Hippo Valley, which are now owned by black farmers but as out-growers for Tongaat Hullet. The crucial question addressed in the thesis is whether the A2 sugar cane farmers and their workers, located at the production end of the sugar cane global value chain, are benefitting from their involvement in this value chain. A number of scholars argue that global value chains lead to economic and social upgrading at the production end of the chain, based on thoughts contained in modernisation and trickledown theory. There is an assumption, then, that integration into the global economy leads to economic upgrading which translates into social upgrading. In drawing upon critical global value theorists, bolstered by the Marxist perspective, considers the importance of a more critical view of global value chains in relation to the sugar cane industry in Zimbabwe, with the particular focus on A2 farms. Thus, the main objective of the thesis is to consider the lives and livelihoods of A2 sugar cane farmers and sugar cane workers through a case study, in the context of global value chains and arguments around economic and social upgrading. This is pursued through a case study of six A2 farms, which involved interviewing farmers, supervisors, and both permanent and temporary workers. The thesis concludes that there is no significant evidence of social upgrading amongst the labour force, and that the A2 farmers are in constant tension with Tongaat Hullet in seeking to engage in economic upgrading of their status as commercial farmers.
Keywords: International trade; Sugar trade -- Zimbabwe; Sugar growing -- Zimbabwe -- Social aspects; Agriculture -- Zimbabwe -- Social aspects